ADHD medicine consumption in Europe after COVID-19: catch-up or trend change? - Gimbach, Sophie; Vogel, Daniel; Fried, Roland; Faraone, Stephen V.; Banaschewski, Tobias; Buitelaar, Jan; Döpfner, Manfred; Ammer, Richard (BMC psychiatry, 2024)
Background: Although the COVID-19 pandemic and its implications have been associated with mental health services utilization and medication consumption, there is no longitudinal study on the long-term impact on ADHD medication use trends. Methods: This study examines the European ADHD medication consumption in 2020 to 2022 compared to the predicted consumption assuming the persistence of pre-pandemic trends. Predictions are calculated using Seasonal Autoregressive Integrated Moving Average (SARIMA) models. Results: While European ADHD medication sales recorded a drop in 2020, they returned to the predicted level in 2021, even slightly exceeding it. In 2022, we found a clear exceedance of the predicted level by 16.4% on average at country level. Furthermore, the increase in consumption growth in the post-pandemic period (2021–2022) compared to the pre-pandemic period (2014–2019) was significant in 26 of the 28 European countries under consideration. Conclusion: There is strong evidence of a trend change in the ADHD medicine consumption growth throughout Europe after the COVID-19 pandemic.